Adhesion Class GPCRs in GtoPdb v.2021.3. (2021) - Arac-Ozkan, Demet; Aust, Gabriela; Bonner, Tom I.; Cappallo-Obermann, Heike; Formstone, Caroline; Hamann, Jörg; Harty, Breanne; Heyne, Henrike; Kirchhoff, Christiane; Knapp, Barbara; Krishnan, Arunkumar; Langenhan, Tobias; et al.
No abstract available